Alur Distribusi Pemasaran Sayur Organik Di CV. Reja Mayur - Alifia Iga Sutrisno; Nuriah Yuliati (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
Vegetables are a food that is needed by humans because it has a high nutritional content and is needed by the body every day. Organic vegetable farming has attracted attention with the development of agricultural science that has been practiced by humans. Every year there is a shift in the landscape of organic farming in Indonesia. CV. Reja Mayur is a company that sells organic agricultural products under the name Twelve's Organic. Marketing is a comprehensive and planned activity of a company that makes various efforts to meet market demand. Marketing channels are generally a collection of organizations and institutions involved in the distribution of goods and services. The purpose of this study is to describe the marketing distribution flow of organic vegetables at CV Reja Mayur. Descriptive analysis is the analysis method used in this research. Interviews and active participants were the data collection methods used. Three marketing distribution channels were identified by the findings of this study: farmer-consumer, farmer-supermarket (hokky)-consumer, and farmer-retailer-consumer.